2012
DOI: 10.1007/s10930-012-9409-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Recombinant Ecarin

Abstract: The snake venom protease ecarin from Echis carinatus was expressed in stable transfected CHO-S cells grown in animal component free cell culture medium. Recombinant ecarin (r-ecarin) was secreted from the suspension adapted Chinese Hamster Ovary (CHO-S) host cells as a pro-protein and activation to the mature form of r-ecarin occurred spontaneously during continued incubation of the cell culture at 37 °C after death of the host cells. Maximal ecarin activity was reached 7 days or more after cell culture viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
4
15
0
Order By: Relevance
“…Our characterization of recombinant ecarin confirmed that r-ecarin could efficiently generate thrombin without any additional co-factors 13 - 15 . We found that although the primary product from digesting prothrombin with ecarin is meizothrombin, the meizothrombin was very rapidly converted to thrombin, and therefore the final product is thrombin.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Our characterization of recombinant ecarin confirmed that r-ecarin could efficiently generate thrombin without any additional co-factors 13 - 15 . We found that although the primary product from digesting prothrombin with ecarin is meizothrombin, the meizothrombin was very rapidly converted to thrombin, and therefore the final product is thrombin.…”
Section: Resultssupporting
confidence: 65%
“…In parallel with expressing and characterizing trocarin and oscutarin we also produced and characterized recombinant ecarin from CHO cells as was recently described 13 . Our characterization of recombinant ecarin confirmed that r-ecarin could efficiently generate thrombin without any additional co-factors 13 - 15 .…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Prethrombin-2, structurally has one glycosylation site (at Asn373) and four disulphide bonds (Cys293-Cys439, Cys348-Cys364, Cys493-Cys507, and Cys521-Cys551) (Soejima et al, 2001). Pretrombin-2 can be converted to thrombin by FXa enzyme activators (Owen et al 1974), or with ecarin, namely metalloprotease in the venom of snake Echis carinatus species (So et al 1992;DiBella et al 1995;Jonebring et al 2012;Yonemura et al 2004;Subroto et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is an effort to express a recombinant h u m a n p r e t h r o m b i n -2 ( r h P T 2 ) h o s t e d b y microorganisms, such Escherichia coli for commercial purposes (Choi et al 1989;So et al 1992;Silaban et al 2014). However, activation of rhPT2 into thrombin via proteolytic cleavage of FXa is replaced by ecarin, the snake venom protease isolated from Echis carinatus (Jonebring et al 2012). The activated rhPT2 needs further purification to remove ecarin, hence decreasing the production efficiency.…”
mentioning
confidence: 99%